Retinal Photography Screening Programs to Prevent Vision Loss from Diabetic Retinopathy in Rural and Urban Australia: A Review. (12th December 2014) - Tapp, Robyn J.; Svoboda, Jean; Fredericks, Bronwyn; Jackson, A. Jonathan; Taylor, Hugh R.
ABSTRACT: Purpose : This review assessed the effectiveness of diabetic retinopathy (DR) screening programs, using retinal photography in Australian urban and rural settings, and considered implications for public health strategy and policy. Methods : An electronic search of MEDLINE, PubMed, and Embase for studies published between 1 January 1996 and the 30 June 2013 was undertaken. Key search terms were "diabetic retinopathy, " "screening, " "retinal photography" and "Australia." Results : Twelve peer-reviewed publications were identified. The 14 DR screening programs identified from the 12 publications were successfully undertaken in urban, rural and remote communities across Australia. Locations included a pathology collection center, and Indigenous primary health care and Aboriginal community controlled organizations. Each intervention using retinal photography was highly effective at increasing the number of people who underwent screening for DR. The review identified that prior to commencement of the screening programs a median of 48% (range 16–85%) of those screened had not undergone a retinal examination within the recommended time frame (every year for Indigenous people and every 2 years for non-Indigenous people in Australia). A median of 16% (range 0–45%) of study participants had evidence of DR. Conclusions : This review has shown there have been many pilot and demonstration projects in rural and urban Australia that confirm the effectiveness of retinal photography-based screening for DR.